Erythroid spectrin binding modulates peroxidase and catalase activity of heme proteins. Issue 5 (4th March 2022) - Bose, Dipayan; Aggarwal, Shantanu; Das, Debashree; Narayana, Chandrabhas; Chakrabarti, Abhijit
Abstract: Hemoglobin oxidation due to oxidative stress and disease conditions leads to the generation of ROS (reactive oxygen species) and membrane attachment of hemoglobin in‐vivo, where its redox activity leads to peroxidative damage of membrane lipids and proteins. Spectrin, the major component of the red blood cell (RBC) membrane skeleton, is known to interact with hemoglobin and, here this interaction is shown to increase hemoglobin peroxidase activity in the presence of reducing substrate ABTS (2′, 2′‐Azino‐Bis‐3‐Ethylbenzothiazoline‐6‐Sulfonic Acid). It is also shown that in the absence of reducing substrate, spectrin forms covalently cross‐linked aggregates with hemoglobin which display no peroxidase activity. This may have implications in the clearance of ROS and limiting peroxidative damage. Spectrin is found to modulate the peroxidase activity of different hemoglobin variants like A, E, and S, and of isolated globin chains from each of these variants. This may be of importance in disease states like sickle cell disease and HbE‐β‐thalassemia, where increased oxidative damage and free globin subunits are present due to the defects inherent in the hemoglobin variants associated with these diseases. This hypothesis is corroborated by lipid peroxidation experiments. The modulatory role of spectrin is shown to extend to other heme proteins, namely catalase and cytochrome‐c. Experiments with free heme and Raman spectroscopy of heme proteins in the presence of spectrin show that structural alterations occur in the heme moiety of the heme proteins on spectrin binding, which may be the structural basis of increased enzyme activity.